1988
DOI: 10.1155/lc.9.369
|View full text |Cite
|
Sign up to set email alerts
|

The Production of IF(B3Π) in the248 nm Laser Photolysis ofFluorine/Alkyl Iodide Mixtures

Abstract: Sustained visible emission in the region 440–850 nm from the B → X system of IF is observed when a gas phase mixture (~0.5 mbar) of an alkyl iodide with F2 in He is photolysed at 248 nm by a KrF laser. The total intensity and decay rate of the IF(B) emission is a strong function of the identity of the alkyl iodide and can be correlated with the 248 nm photon yields for the production of I*(2p1/2). The half-lives for the IF(B) decays range from 5 μs for t-C4H9I to 770 μs for n-C3F7I. Decay curves for the I*(2p1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These variations are somewhat smaller than those observed experimentally. The bandwidth of 0.01 cm"1 is the minimum spectroscopic bandwidth possible for a 6-Torr sample of this molecule on the basis of the pressure broadening of approximately 1 cm"1/atm observed in high-resolution fundamental spectra.31 At this narrow bandwidth, only [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] transitions contribute to the excited-state population. These calculations suggest that even significant variation of the excited distribution (major errors in the simulation) is unlikely to account for the discrepancy between calculations and experimental data.…”
Section: £~-£[^+(Hh <6>mentioning
confidence: 99%
See 1 more Smart Citation
“…These variations are somewhat smaller than those observed experimentally. The bandwidth of 0.01 cm"1 is the minimum spectroscopic bandwidth possible for a 6-Torr sample of this molecule on the basis of the pressure broadening of approximately 1 cm"1/atm observed in high-resolution fundamental spectra.31 At this narrow bandwidth, only [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] transitions contribute to the excited-state population. These calculations suggest that even significant variation of the excited distribution (major errors in the simulation) is unlikely to account for the discrepancy between calculations and experimental data.…”
Section: £~-£[^+(Hh <6>mentioning
confidence: 99%
“…13,14 The same group has also produced IF(B) emission by 248-nm photolysis of alkyl iodide/F2 mixtures. 15,16 From the results of these studies13"16 it has been suggested that IF(B) is formed either by the recombination of I*(2P1/2) and F atoms or by sequential excitation of IF(X) by I*. A definitive interpretation has been precluded by a lack of understanding of F2/alkyl iodide dark reaction kinetics, although Davis and Woodward have recently established the steps by which 02(' ) sequentially pumps IF(X) to IF(B).6 Some cursory studies of the reaction between F2 and the alkyl iodides have been made.…”
Section: Introductionmentioning
confidence: 99%